2015
DOI: 10.1179/1743289815y.0000000016
|View full text |Cite
|
Sign up to set email alerts
|

Influence of banana stem powder on knotty tear behaviour of prevulcanised natural rubber latex composite films

Abstract: Prevulcanised natural rubber latex (PvNRL)/banana stem powder (BSP) composite films were prepared by adding various amounts of 10%BSP dispersion. The properties of the resulting prevulcanised (PvNRL)/BSP composite films were compared with those films containing the same amounts of calcium carbonate (CaCO 3 ). The PvNRL/BSP composite films have higher swelling index but lower tensile properties compared to the films containing CaCO 3 . However, PvNRL/BSP composites films containing more than 10 parts per hundre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…Fillers either naturally occur in a form of fine particles or are subjected to grinding. In the literature of the subject one can find numerous examples of natural fillers, including rice bran [16], banana powder [14], argan nut shell [5], vanilla [9], wood powder [4], switch grass [11], and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Fillers either naturally occur in a form of fine particles or are subjected to grinding. In the literature of the subject one can find numerous examples of natural fillers, including rice bran [16], banana powder [14], argan nut shell [5], vanilla [9], wood powder [4], switch grass [11], and many more.…”
Section: Introductionmentioning
confidence: 99%
“…Rice husk powder was also examined in other studies (Hardinnawirda and SitiRabiatull Aisha 2012;Ramasamy et al 2013), where the authors found that the rice husk powder acted as a reinforcing filler. Another example of the application of natural fillers is the study conducted by Nuraya et al (2015), in which a research team compared rubber compounds containing banana powder and calcium carbonate as the filler. It was concluded that despite a poorer tensile strength, the mixture containing banana powder exhibited a greater tear strength.…”
Section: Introductionmentioning
confidence: 99%
“…The adhesion on the polymer-filler interface is significant and often has a decisive impact on properties of polymer blends. Polymer adhesion depends on the conditions of polymer absorption on filler surface, filler grain wettability by polymer melt, and bonds created between filler and polymer [24]. Table 5 illustrates the relationship between strain at maximum tensile stress and the applied contents of the filler in the form of powder made of ground pumpkin seed hulls.…”
Section: Strength Tests Of Produced Injection Molded Piecesmentioning
confidence: 99%